Participatory worlds: audience participation in fictional worlds - Blázquez, José M. (2018)
Consumer participation in the production of information, knowledge and culture has become increasingly popular in the last three decades. Although these participatory practices have been successfully incorporated into business models in many sectors, media and entertainment industries are still quite reluctant to invite audiences to create canonical content for their storyworlds. Media conglomerates hold a firm grip over their intellectual property and only allow selected parties to participate in the production of official content for their franchises. In contrast, participatory worlds are fictional worlds which allow audiences to contribute with canonical additions to their expansion. In participatory worlds, audience members are welcome to contribute to the content production chain and/or decision-making processes, having the chance to become contributors and co-authors of the texts. This thesis critically examines participatory worlds with the aim of understanding what they are and how they operate within the industrial context. This research introduces two models of participatory worlds, the ‘sandpit’ and ‘spin-off’ models, based on the location and medium where audience participation takes place, primary or ancillary works, and uses one case study to illustrate each of these: the massively multiplayer online role-playing game (MMORPG) Lord of the Craft (2011- ) and Grantville Gazette (2003- ), an e-zine rooted in the 1632 Universe. These case studies are compared with commodities produced and systems employed by media conglomerates in the management and canonical expansion of their fictional worlds in order to establish similarities and differences among them and determine where participatory worlds stand in respect to the media and entertainment industries. The concept of ‘intervention’ is introduced to define the capabilities that audience members are given to contribute canonically and make an impact in a storyworld. This thesis explores the factors which determine the degree of ‘intervention’ given to participants in participatory worlds by examining two further case studies, the web drama Beckinfield (2010-2013) and the TV show Bar Karma (2011), in addition to the aforementioned. The comparison of the four case studies reveals different approaches to audience participation within these practices.